2008
DOI: 10.1029/2006tc002046
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene high and rapid surface uplift and its erosional response in the Andes of central Chile (33°–35°S)

Abstract: We address the question of the late Cenozoic geomorphological evolution of the central Chile Andes (33°–35°S), using uplift markers, river incision, previous and new ages of volcanic bodies, and new fission track ages. The uplift markers consist of relicts of high elevated peneplains that evidence >2 km of regional surface uplift lasting ∼2 Ma with variable amount along an E‐W transect. The eastern Coastal Cordillera was uplifted 1.5–2.1 km at 33–34°S and <1 km at 35°S, the western Principal Cordillera was upl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
128
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 60 publications
16
128
0
8
Order By: Relevance
“…However, Finger et al (2007) also correlated the mollusk fauna with well dated late Oligocene to middle Miocene occurrences in Peru (see also DeVries and Frassinetti, 2003) and concluded that the older mollusk fauna was reworked during the latest Miocene to early Pliocene. Reconstructions of the tectonic history of the Navidad and Arauco areas (Melnick and Echtler, 2006;Encinas et al, 2008;Farías et al, 2008) support a history of tectonic downwarp and uplift as outlined by Finger et al (2007). Our localities are the same as those of Finger et al (2007) and locality data including GPS points (Table 1), detailed strontium data for individual samples and localities (Table 2), and representative sample photos (Fig.…”
Section: Geologic Setting and Sampling Sitesmentioning
confidence: 70%
See 1 more Smart Citation
“…However, Finger et al (2007) also correlated the mollusk fauna with well dated late Oligocene to middle Miocene occurrences in Peru (see also DeVries and Frassinetti, 2003) and concluded that the older mollusk fauna was reworked during the latest Miocene to early Pliocene. Reconstructions of the tectonic history of the Navidad and Arauco areas (Melnick and Echtler, 2006;Encinas et al, 2008;Farías et al, 2008) support a history of tectonic downwarp and uplift as outlined by Finger et al (2007). Our localities are the same as those of Finger et al (2007) and locality data including GPS points (Table 1), detailed strontium data for individual samples and localities (Table 2), and representative sample photos (Fig.…”
Section: Geologic Setting and Sampling Sitesmentioning
confidence: 70%
“…A related shift from tectonically erosive to accretionary conditions along the offshore forearc of South-central Chile during the Pliocene was proposed to have led to inversion of existing forearc basins (Melnick and Echtler, 2006). Significant Late Miocene to Pliocene uplift is documented also by fission track data, both from the Navidad and Arauco areas (Farías et al, 2008;Glodny et al, 2008). It thus seems reasonable that Mid-Miocene and later tectonic processes along the Chilean continental margin and in the Southern Andes had already stopped sedimentation in near-coastal Navidad-like basins at ~16 Ma, which would account for the lack of younger mollusk ages in our sample set and along the South-Central Chilean coast in general.…”
Section: Climate Paleoceanography and Tectonicsmentioning
confidence: 86%
“…This meridional precipitation gradient is collocated with a gradient in terrain elevation: the Andes mean height decreases from about 4500 m MSL at 308S down to 1500 m MSL at 408S. Some authors in the geological community have speculated that the inverse relationship between precipitation and the Andes' elevation is rooted in a long-term relationship between climate, erosion, and tectonics [see Farías et al (2008) for a review]. The narrow strip of land between the Andes and the Pacific coast also concentrates about 10 million inhabitants, about 70% of the Chilean population, so understanding the orographic control of precipitation along central Chile is an important practical issue.…”
Section: Introductionmentioning
confidence: 99%
“…The igneous activity completely ceased by the late Pliocene along the western flank of the Principal Andean Cordillera, except for the currently active Southern Volcanic Zone of the Andes, which developed since the latest Pliocene farther east along the continental watershed. Basin inversion and significant tectonic uplift of the Principal Andean Cordillera took place as a result of the Neogene compressive tectonism Sillitoe and Perelló (2005) with fold and thrust belt and synorogenic deposits from Ramos et al (1996) and faults in Chile from Farías et al (2008); the projection of the axis of the Juan Fernández Ridge after Gilbert et al (2006). (Godoy et al, 1999;Charrier et al, 2002Charrier et al, , 2005, but also the synchronous development of a foreland basin system farther east in Argentina (Giambiagi et al, 2001).…”
Section: Geological Frameworkmentioning
confidence: 99%